2005
DOI: 10.1523/jneurosci.2672-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Juxtacellular Recording/Labeling Analysis of Physiological and Anatomical Characteristics of Rat Intergeniculate Leaflet Neurons

Abstract: The thalamic intergeniculate leaflet (IGL) is involved in mediating effects of both photic and nonphotic stimuli on mammalian circadian rhythms. IGL neurons containing neuropeptide Y (NPY) have been implicated in mediating nonphotic effects, but little is known about those involved in photic entrainment. We used juxtacellular recording/labeling in rats to characterize both photic responses and neurochemical phenotypes of neurons in the lateral geniculate area, focusing on the IGL and ventral lateral geniculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 64 publications
(96 reference statements)
3
32
0
Order By: Relevance
“…Staining for neuropeptide Y (NPY) in the IGL is much stronger than that for surrounding regions (Card and Moore, 1989;Morin et al, 1992;Moore and Card, 1994;Thankachan and Rusak, 2005). In our experiments, the NPY-labeled IGL (see Fig.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Staining for neuropeptide Y (NPY) in the IGL is much stronger than that for surrounding regions (Card and Moore, 1989;Morin et al, 1992;Moore and Card, 1994;Thankachan and Rusak, 2005). In our experiments, the NPY-labeled IGL (see Fig.…”
Section: Methodsmentioning
confidence: 59%
“…Burst spike firing can be evoked in IGL neurons in vivo by retinal illumination (Ying et al, 1993;Thankachan and Rusak, 2005), and rhythmic oscillations can spontaneously occur under constant light (Werhun and Lewandowski, 2009) and can be evoked in slices by optic stimulation (Blasiak et al, 2009). Here we demonstrated that IGL neurons spontaneously fired LTS bursts when the membrane was hyperpolarized; such burst firing formed a rhythmic oscillation with a burst frequency of 0.5-2.6 Hz (Fig.…”
Section: Functional Expression Of Hcn3 Channels Contributes To Rhythmmentioning
confidence: 99%
“…However, light induces c-Fos mainly in non-immunoreactive cells. Recently, using juxtacellular recordings/labelling methods and NPY immunostaining, Thankachan and Rusak (2005) have classified three types of cells, which respond differently to retinal illumination, in the rat IGL. Type I neurons lacking NPY show sharp increases in firing at light onset, sustained activation during continued illumination and moderate firing rates in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…Both types are likely involved in mediating IGL photic adjustments to SCN. In contrast, type II neurons presented large NPY amounts and heterogeneous response to illumination and mediate the IGL non-photic function (Thankachan and Rusak 2005). Since we found a decrease in both IGL retinal projections and NPY-IR, we believe these three types of IGL neurons are functionally disrupted within the aging process, type I and type III in its activation by light input and type II in NPY expression, which points the adjustments IGL provides to central clock, by integration of photic and non-photic clues, are hindered with aging.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, Thankachan and Rusak (2005) characterized three classes of IGL neurons according to its activation by light and NPY presence. Among these classes, type I and type III neurons presented sustained activation by light and absence of NPY synthesis, differing in activation during darkness.…”
Section: Discussionmentioning
confidence: 99%